The impact of danger in the element material of the crime - الشمري, كاظم عبد الله; كاظم, رشا علي (Journal of Legal Sciences, 2019)
The idea of ​​danger is of particular importance in the design of modern criminal Politics, especially in relation to places that are at the core of the principles of criminal legislation, which are the extent of its importance and its connection to crime and its physical structure in all its components.             Most criminal legislation takes the danger of a Basis and a criminalization code, reflecting the criminal legislator's keenness to provide greater protection for the fundamental interests of the society. This protection is important and necessary, since it is often possible to wait for the harmful consequences of unlawful conduct.            In fact, the legislator does not criminalize dangerous behavior unless the danger reaches a large sum so as not to increase the crimes in violation of the law, threaten the freedoms, and thus lead to inflation, criminalization, and punishment, so as not to affect the social activities desired to develop the system of society as a whole.             The danger in our research is a characteristic of the physical element of the crime, since this element contains elements of behavior, result and Causation between them. Therefore, the risk may be caused by behavior or by the result or causal link. The relationship of risk to behavior is different and distinct from its relation to outcome and causality, so we will show how danger is introduced in determining positive or negative behavior, as well as in the outcome and its role in causation.